Adaptability Evaluation of Vocational Education and Economic Development Under the Bipolar Neutrosophic Sets - Chen Yuan; Yongye Chen (Neutrosophic Sets and Systems)
This study suggests a decision-making methodology to evaluate the risks in vocational education and economic development. This problem has different criteria and alternatives which must be evaluated. This evaluation can include uncertainty in the evaluation process. So, we use the bipolar neutrosophic sets (BNSs) to deal with uncertainty and vague data. The BNSs are extensions of the neutrosophic sets. We used two decision-making methods for the evaluation of risks in vocational education and economic development such as BWM to compute the criteria weights and the COPRAS method to rank the alternatives based on a set of criteria. This study uses nine criteria and six alternatives. The results show that Public Vocational Training Institutions is the best alternative and the Corporate Training and Upskilling Programs is the worst alternative.